Histórias de vida e perspectivas de futuro de educandos do Programa Ação Integrada Adultos do CMEB Maria Lygia Andrade Haack - Silva, Márcia Regina da (Universidade do Vale do Rio dos Sinos, 2016)
In the dissertation we investigate the life story and the prospects of future from adult students who return to schooling. The survey has been developed in a school situated in the city Esteio, Rio Grande do Sul. The searched group belonged to a program called Integrated Action Adults, in the modality Education of Youth and Adults. The methodology used in the process was: mapping out of the class data; documental analysis (school's Political Pedagogical Plan and regiment of the Integrated Action Adults Programme); research of qualitative approach based on empirical observations of the group of students (classroom, quarterly socializations and graduation ceremony); semi-structured interviews with a sample of students and with the class teacher and analysis of data by categories as well. Among theorists that subsidized the analysis are included references of Paulo Freire, Álvaro Vieira Pinto and Miguel Arroyo. The objectives of this research were: to contextualize the reality and the life story of the surveyed subjects; to analyze the extent to which learners plan their future after their reentry into school; to observe and to analyze the importance that school has for learners; to establish relationships between the acquired knowledge within and outside the school by the students. This investigative work has allowed the reflection on this mode of teaching and how much it interferes in the students life and in the life of professionals that are part. While carrying out the research a diverse public has been met, each one with his experiences, his stories, his expectations, his difficulties and his projects for the future. It has been reinforced the understanding that Education needs to be based on the valuing of what every student knows, so that significant learning can happen, individually and collectively.
Keywords: Educação de jovens e adultos; Histórias de vida; Perspectivas de futuro; Programa ação integrada adultos; Education of youth and adults; Life stories; Prospects of future; Integrated action adults programme; ACCNPQ::Ciências Humanas::Educação